Formation and Transitions of Consumption Culture: A Study Within a Veiled Youth Population - Aydin-Unal, Duygu (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This article answered how the existing consumption practices are shaped among the newly formed consumers. In this direction, veiled youths, who are a large consumer group in Turkey, were selected as a sample. The face-to-face interviews with young people were conducted, and semiotic analysis of the Instagram accounts that interviewers were influenced were analyzed. As results revealed, consumption trends of this group, which is growing both as market and consumer size, can be gathered under four headings. These are the interpretation of popular cultures through consumption, transforming consumption practices and their symbols, seeking to acquire authenticity and status, conspicuous consumption tendencies and interpretation of popular culture through. These findings present a substantial discussion regarding the transformation of consumer classes. Keywords: Consumption culture; veiled youth; symbolic meanings, popular culture